IMPACT OF MUD BRICK MAKING ON THE PERI-URBAN ENVIRONMENTS OF MUKONO DISTRICT, UGANDA (FUDMA JOURNAL OF SCIENCES, 2021)
The study investigated the impact of mud-brick making on the wetland ecosystem in Mukono district. The major objectives of the study were to establish the impact of brick making on the peri-urban environment in Mukono District Uganda. The study properly evaluated the socio-economic factors that influence the reliance of the people in the peri-urban area on brick making and wood selling in wetland. The data was collected between August 2019 to February 2021 by administering a structured questionnaire to 50 respondents that comprised brick makers, brick buyers, Local Council Executive, tree farmers, fuel wood sellers and District Environmental Executives that were randomly selected. Several socio-economic factors such as distance from the wetland, age, land owner ‘s major income, level of education and the amount of fire wood used during the mud-brick making process were analyzed. Result showed that brick-making process and impact to the peri-urban environment exposed significantly (P
Keywords: Environment, Brick-making, Conservation, Wetland, Peri-urban, Socio-economic